2015
DOI: 10.1111/ijcp.12713
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the use of demeclocycline in the treatment of hyponatraemia secondary to SIADH : a systematic review

Abstract: SummaryAimsHyponatraemia (HN) is the most common electrolyte balance disorder in clinical practice. Since the 1970s, demeclocycline has been used in some countries to treat chronic HN secondary to syndrome of inappropriate antidiuretic hormone secretion (SIADH). The precise mechanism of action of demeclocycline is unclear, but has been linked to the induction of nephrogenic diabetes insipidus. Furthermore, the safety profile of demeclocycline is variable with an inconsistent time to onset, and a potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…DMCT kill bacteria by binding to ribosomes inhibiting protein synthesis. It is used as a broad-spectrum antibiotic, but may be more often used to treat chronic syndrome of inappropriate secretion of antidiuretic hormone (SIADH) ( Miell et al, 2015 ). According to reports, DMCT is expected to be used as a contrast agent for intraoperative detection of brain tumors ( Sarkar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DMCT kill bacteria by binding to ribosomes inhibiting protein synthesis. It is used as a broad-spectrum antibiotic, but may be more often used to treat chronic syndrome of inappropriate secretion of antidiuretic hormone (SIADH) ( Miell et al, 2015 ). According to reports, DMCT is expected to be used as a contrast agent for intraoperative detection of brain tumors ( Sarkar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mode of action is not well understood, it can induce nephrogenic diabetes insipidus, and a recent systematic review reported that demeclocycline was able to increase sodium levels in about 60% of patients with hyponatraemia secondary to SIADH (7). However, the onset of action is unpredictable and varies between 2 and 5 days (7). The effect is considered to be milder than that of the vaptans, and it is questionable whether this would have enabled us to hyperhydrate our patient.…”
Section: Discussionmentioning
confidence: 99%
“…30 The use of oral medications such as demeclocycline and lithium, which act to decrease the responsiveness of the vasopressin receptor to ADH and thereby increasing water excretion, is limited by nephrotoxicity and delay in treatment to response by several days to 1 week. 31 In those with severe hyponatremia requiring more rapid correction, administration of IV sodium chloride may be required. It is important to understand, for sustained sodium increase, the sodium concentration of the IV fluid must exceed the concentration in the urine.…”
Section: Syndrome Of Inappropriate Antidiuretic Hormone Secretionmentioning
confidence: 99%